Primary structure of a PLA2 , deduced from mRNA extracted from whole venom of Crotalus durissus terrificus - Ronald Navarro Oviedo (2017)
From the whole venom of Crotalus durissus terrificus from, Tambopata-Madre de Dios, mRNA encoding a fosfolipase A2 (PLA2) protein has been isolated, using a simple technique. That is, cDNA encoding the PLA2 D49, has been amplified by RT-PCR.Analysis of cDNA encoding PLA2, has shown that this open reading frame of 414 bp encoding a polypeptide of 138 amino acids with a signal peptide of 16 amino acid residues, followed by a polypeptide sequence of 122 amino acids corresponding to PLA2. The analysis also shows that the protein is composed of 33 charged amino acids: 11 amino acids acidic, 20 basic amino acids, 44 polar amino acids and 28 hydrophobic amino acids, having an isoelectric point of 8.58 and a molecular mass of 14312.52 Da. The homology and phylogenetic tree analysis shows that this PLA2 has a high degree of homology and belongs to the basic PLA2 N6F24D49.